1996
DOI: 10.1177/1532673x9602400301
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of School Desegregation Plans, 1968-1991

Abstract: A major debate in school desegregation policy is whether voluntary, market-based mechanisms (such as magnet schools) result in more school desegregation than command-and-control approaches (such as mandatory reassignment). Using data obtained from a national probability sample of 600 school districts, we explore the effects of different types of desegregation plans on White flight, racial imbalance, and interracial exposure from 1968 to 1991 Based on the results of multiple regression analyses, we find that (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 12 publications
1
45
0
Order By: Relevance
“…In contrast, Lutz (2011) finds that the termination of court-ordered busing plans beginning in the early 1990s led to virtually no short-run change in the exposure index, and a 10-year change of about 3.5 percentage points. In CMS, the change in the exposure index from 2001-2 to 2008-9 was about 13 percentage points, which is similar in magnitude to the effect of court-ordered desegregation in the 1960s and 1970s (Rossell and Armor 1996;Guryan 2004).…”
Section: Quarterly Journal Of Economicssupporting
confidence: 52%
See 1 more Smart Citation
“…In contrast, Lutz (2011) finds that the termination of court-ordered busing plans beginning in the early 1990s led to virtually no short-run change in the exposure index, and a 10-year change of about 3.5 percentage points. In CMS, the change in the exposure index from 2001-2 to 2008-9 was about 13 percentage points, which is similar in magnitude to the effect of court-ordered desegregation in the 1960s and 1970s (Rossell and Armor 1996;Guryan 2004).…”
Section: Quarterly Journal Of Economicssupporting
confidence: 52%
“…First, the rezoning of CMS schools led to changes in segregation that were considerably larger than the average district in Lutz (2011). The seven-year change in the exposure index (a commonly used measure of segregation) was about 13 percentage points, which is nearly as large as the effect of court-ordered desegregation in the 1960s and 1970s (Rossell and Armor 1996;Guryan 2004). Second, studentlevel data from a single district coupled with a quasi-experimental research design allow us to explore how changes in school racial composition might affect students through different mechanisms such as school resources and peer effects (Reber 2010;Cascio et al 2010;Johnson 2011;Bifulco et al 2011;Imberman et al 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Welch and Light (1987) and Rossell and Armor (1996) show that the implementation of desegregation plans led to an increase in the speed of migration of whites out of urban school districts. If there is a similar phenomenon among blacks, the previous estimates are compromised.…”
Section: Selective Migrationmentioning
confidence: 99%
“…Several studies have shown that past efforts to desegregate schools generated "white flight" from U.S. central cities (Clotfelter, 1979;Coleman, Kelly & Moore, 1975;Rossell & Armor, 1996;Welch & Light, 1987). The ability of white parents to avoid school desegregation efforts by changing where they live differs substantially across the country due to differences in the relative size of central city school districts.…”
Section: Preferences Based On Race and Classmentioning
confidence: 99%